Perbedaan hasil belajar dan self-efficacy pada siswa yang diberikan feedback setelah penggunaan Quizizz dengan Plickers - Fitria Oktafianti; Dadang Machmudin; Kusnadi Kusnadi (Assimilation: Indonesian Journal of Biology Education, 2021)
This study aims to determine the differences learning outcomes and self-efficacy in students are given feedback after the use of Quizizz with Plickers. This research used a quasi-experimental method with a nonequivalent control group research design. Subjects in this research are the students of eleven grade of SMAN 10 Bandung. XI IPA 6 as an experimental class 1 was treated by giving feedback after using Quizizz, XI IPA 5 as an experimental class 2 was treated by giving feedback after using Plickers, and XI IPA 1 as a control class. The instrument in this research uses multiple-choice pre-test and post-test questions to measure cognitive learning outcomes and questionnaire statements to measure self-efficacy and saw students' responses to learning activities and evaluation tools used. The result of this research showed that there were differences learning outcomes and self-efficacy in students are given feedback after the use of Quizizz with Plickers. The class that were given feedback after using Quizizz showed higher average learning outcomes and higher percentage of self-efficacy compared to other classes. In addition, students' responses to learning activities and evaluation tools used were more positive in the class given feedback after using Quizizz compared to other classes.